The Bad Guys in open wide and say arrrgh! - Blabey, Aaron (Blabey, Aaron. Bad guys, 2022)
"WEIRD?! Nothing weird EVER happens in The Bad Guys. Like, you would NEVER see a chain-saw monster confronting a velociraptor who has eaten an elderly piranha, or the disturbing antics of a deranged dentist running amok with an oversized drill. NOPE. None of that nonsense here. So relax and be entirely unsurprised by the Bad Guys' next adventure!"--Provided by publisher